THE VALUE OF CATUR PURUSA ARTHA AND ENTREPRENEURSHIP ORIENTATION AS A BASE FOR MAXIMIZING SMEs PERFORMANCE - Utami, Ni Made Satya; Sapta, I Ketut Setia; Dicriyani, Ni Luh Gede Mahayu; Astakoni, I Made Purba (Jurnal Aplikasi Manajemen, 2023)
Developed countries understand the importance of small and Medium Enterprises (SMEs) in their contribution to economic growth. By using the concept of cultural values Catur Purusa Artha which is the four most important life goals for Balinese people who have Hindu beliefs, should be used as moral guidelines that will affect the business performance of small and Medium Enterprises and entrepreneurship Orientation behavior. This study was conducted to determine and analyze the effect of Entrepreneurship Orientation on the business performance of small and Medium Enterprises and how the role of Entrepreneurship Orientation in mediating the relationship of Catur Purusa Artha with the business performance of small and Medium Enterprises. The population of the study is the owner or managers of small and Medium Enterprises in Bali Province in 2022 amounted to 61,862 SMEs, and of these samples were conducted with the Slovin approach as many as 397 units of SMEs. The data analysis technique is done by the SEM-PLS method. The results found that applying the cultural values of Catur Purusa Artha can have a direct (positive) effect or can increase the business performance of small and Medium Enterprises and Entrepreneurship Orientation. So, doing Entrepreneurship Orientation will also be able to directly affect the performance of small and medium business performance. If doing Entrepreneurship Orientation can also mediate the relationship of Catur Purusa Artha with the business performance of small and Medium Enterprises.